Compact ACS‐fed CRLH MIMO antenna for wireless applications. Issue 6 (28th February 2018) - Ibrahim, Ahmed A.; Abdalla, Mahmoud A.; Hu, Zhirun
Abstract : This study introduces a compact asymmetric coplanar strip (ACS)‐fed composite right–left‐handed (CRLH) multiple‐input–multiple‐output (MIMO) antenna for multiband operation. The ACS fed MIMO antenna is composed of two elements; each is operating at 5, 5.8 and 6.3 GHz; for different wireless applications. The overall MIMO antenna size is compact (46 × 26 mm 2 ). A unit cell of the CRLH connected to 50 Ω ACS fed is considered the main block of the antenna. The edge‐to‐edge separation between antenna elements equals 0.4 λ 0 at 5 GHz. The insertion loss, correlation coefficient, diversity gain and channel capacity are used to evaluate the performance of the ACS‐fed MIMO antenna. The isolation higher than 25 dB and envelope correlation lower than 0.05 have been achieved without using any extra decoupling structures. The experimental results are reasonably well agreed with simulated ones.